A novel quantification tool for elastane in textiles using thermal treatment. (15th January 2023) - Boschmeier, Emanuel; Archodoulaki, Vasiliki-Maria; Schwaighofer, Andreas; Lendl, Bernhard; Bartl, Andreas
Abstract: Elastane, also known as spandex, is a synthetic polymer fibre based on polyurethane, which is present in low amounts in numerous textile products. It is used frequently particularly in sportswear and underwear, because of its stretchability and body-shaping properties. The currently commonly-used standardized elastane quantification method has many outstanding disadvantages, however ongoing production processes as well as upcoming recycling processes rely on it. This study presents a faster, more reliable and more eco-friendly tool to detect and quantify elastane in textiles using differential scanning calorimetry (DSC). An elastane quantification tool (EQT) was developed by studying eleven different elastane samples available on the textile market. The fundament of the EQT is a polymer specific phenomenon, which is investigated in detail by spectroscopic (ATR-FTIR) and thermal (thermogravimetric analysis, DSC) analyses. Ten different textile waste samples from the manufacturing industry and waste collection were selected to test the EQT. Obtained results are very promising, as the elastane contents could be determined quickly and accurately. The EQT has the potential to become a widely used method in the textile production chain, particularly in the upcoming recycling sector. Highlights: Development of a straightforward elastane quantification tool (EQT) for textiles. Result output after only 78 minutes, ideally for production control and upcoming recycling processes. Determination of widely used elastane brands. Proof with different post-industrial and post-consumer textile waste samples.